Neurological Predictors of Clinical Outcomes in Hospitalized Patients With COVID-19 - Salahuddin, Hisham; Afreen, Ehad; Sheikh, Irfan S.; Lateef, Sohaib; Dawod, Giana; Daboul, Judy; Karim, Nurose; Gharaibeh, Khaled; Al-Chalabi, Mustafa; Park, Sihyeong; Castonguay, Alicia C.; Assaly, Ragheb; et al. (Frontiers in Neurology, 2020)
Introduction Multiple risk factors of mortality have been identified in patients with COVID-19. Here, we sought to determine the effect of a history of neurological disorder and development of neurological manifestations on mortality in patients with COVID-19. Methods From March 20 to May 20, 2020, hospitalized patients with laboratory confirmed or highly suspected COVID-19 were identified at four hospitals in Ohio. Previous history of neurological disease was classified by severity (major to minor). Neurological manifestations during disease course were also grouped into major and minor manifestations. Encephalopathy, ischemic or hemorrhagic stroke, and seizures were defined as major manifestations, whereas minor neurological manifestations included headache, anosmia, dysgeusia, dizziness or vertigo, and myalgias. Multivariate logistic regression models were used to determine significant predictors of mortality in patients with COVID-19 infection. Results 574/626 hospitalized patients were eligible for inclusion. Mean age of the 574 patients included in the analysis was 62.8 (SD 17.6), with 298 (51.9%) women. Of the cohort, 240(41.8%) patients had a prior history of neurological disease (HND), of which 204 (35.5%) had a major history of neurological disease (HND) were classified as major. Mortality rates were higher in patients with a major HND (30.9% versus 15.4%; p=0.00002), although this was not a significant predictor of death. Major neurological manifestations were recorded in 203/574 (35.4%) patients during disease course. The mortality rate in patients who had major neurological manifestations was 37.4% compared to 11.9% (p=2x10-12) in those who did not. In multivariate analysis, major neurological manifestation (OR 2.1, CI 1.3-3.4; p=0.002) was a predictor of death. Conclusions In this retrospective study, history of pre-existing neurological disease in hospitalized COVID-19 patients did not impact mortality; however, development of major neurological manifestations during disease course was found to be an independent predictor of death. Larger studies are needed to validate our findings.